Crescent visibility and the challenge to muslim unity in Nigeria (2014)
The unity of Muslims is imperative under the Shari'ah but the sighting of the crescent remains a daunting challenge, sometimes inhibiting this unity. Nigeria is not left out of this challenge as it is confronted with the ideological conflict amongst Islamic scholars in some sections of the country. Whilst studies have been carried out on the disagreement among Islamic scholars on the issue of single or multiple horizon and exclusive reliance or not on astronomy, little seems to have been done about the reconciliatory steps aimed at unity among Islamic scholars in Nigeria with particular reference to disunity about the dates of Islamic rituals. This paper fills the gap through reliance on both primary and secondary sources. Key interviews were conducted with some Islamic scholars. The paper, among other things, suggests the sustenance of the current bridge-building efforts by the Nigerian Muslim community leadership and the synchronisation of science and technology, together with physical effort to determine the actual dates of Islamic festivals.